Tribes and politics in Yemen: a history of the Houthi conflict - Brandt, Marieke (Hurst & Company, 2017)
'Tribes and Politics in Yemen' tells the story of the Houthi conflict in Sa'dah Province, Yemen, as seen through the eyes of the local tribes.